Comparative Analysis of Building Insurance Prediction Using Some Machine Learning Algorithms - Ejiyi, Chukwuebuka Joseph; Qin, Zhen; Salako, Abdulhaq Adetunji; Happy, Monday Nkanta; Nneji, Grace Ugochi; Ukwuoma, Chiagoziem Chima; Chikwendu, Ijeoma Amuche; Gen, Ji (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
In finance and management, insurance is a product that tends to reduce or eliminate in totality or partially the loss caused due to different risks. Various factors affect house insurance claims, some of which contribute to formulating insurance policies including specific features that the house has. Machine Learning (ML) when brought into the field of insurance would enable seamless formulation of insurance policies with a better performance which will also save time. Various classification algorithms have been used since they have a long history and have also got some modifications for optimum functionality. To illustrate the performance of each of the ML algorithms that we used here, we analyzed an insurance dataset drawn from Zindi Africa competition which is said to be from Olusola Insurance Company in Lagos Nigeria. This study therefore, compares the performance of Logistic Regression (LR), Decision Tree (DT), K-Nearest Neighbor (KNN), Kernel Support Vector Machine (kSVM), Naïve Bayes (NB), and Random Forest (RF) Regressors on a dataset got from Zindi.africa competition and their performances are checked using not only accuracy and precision metrics but also recall, and F1 score metrics, all displayed on the confusion matrix. The accuracy result shows that logistic regression and Kernel SVM both gave 78% but kSVM outperformed LR in precision with a percentage of 70.8% for kSVM and 64.8% for LR showing that kSVM offered the best result.
Keywords: machine learning; prediction; regression; IJIMAI